Onfield assessment of concussion in the adult athlete - Putukian, M.; Raftery, M.; Guskiewicz, K.; Herring, S.; Aubry, M.; Cantu, R. C.; Molloy, M. (British Journal of Sports Medicine, 2013)
Background The onfield assessment of concussion in the adult athlete is challenging, given the elusiveness of injury, the sensitivity and specificity of the sideline assessment tools and the evolving nature of concussive injury. This paper reviews the evidence related to the onfield assessment and considers questions related to same day return to play, what to do when no physician is available onsite, as well as the benefit of remote notification of potential concussive events.Objective To review the evidence regarding the onfield assessment of concussion in the adult athlete. Additional key issues to consider include same day return to play for the adult athlete with concussion, what to do in a community setting when no doctor is present and whether there is any benefit with remote notification of potential concussive events that occur on the playing field.Data Sources Systematic literature review of concussion assessment and management. PubMed, MEDLINE, Psych Info and Cochrane Library databases were reviewed using the MeSH key words concussion and mild traumatic brain injury combined with athletic injuries. Each was refined by adding the key words `adult`, `sideline assessment`, `onfield assessment` and `return to play`.Results For the MEDLINE search, using `concussion` and `athletic injuries` as key words, there were 880 results, and refining by `adult` there were 292 results. When `traumatic brain injury` and `athletic injuries` were combined, there were 210 results. When refining by `adult`, there were 89 results. Many of these results overlapped. Following an initial review, these articles form the basis of the discussion.Conclusions The onfield evaluation of sport-related concussion is often a challenge, given the elusiveness and variability of presentation, difficulty in making a timely diagnosis, specificity and sensitivity of the sideline assessment tools and the reliance on symptoms. Despite these challenges, the sideline evaluation is based on recognition of injury, assessment of symptoms, cognitive and cranial nerve function and balance. Serial assessments are often necessary and, since signs and symptoms may be delayed, erring on the side of caution (keeping an athlete out of participation when there is any suspicion for injury) is important. A standardised assessment of concussion is useful in the assessment of the athlete with suspected concussion but should not take the place of the clinician's judgement.